GAMBARAN PERILAKU CUCI TANGAN PADA LANSIA DI WISMA A DAN B PANTI SOSIAL TRESNA WERDHA WISMA BUDI MULIA 2 CENGKARENG JAKARTA BARAT - Lyana Arsianti (STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2021)
One indicator of the success of health development in a country is the increase in the life expectancy of the population. SUSENAS 2014 data, the number of elderly people in Indonesia was 20.24 million in 2014. One of the efforts to improve health status is handwashing behavior. The purpose of this study was to determine the description of hand washing behavior in the elderly at the Tresna Werdha Budi Mulia 2 Social Home in Cengkareng, West Jakarta. The design of this research is simple descriptive. The data collection technique is simple random sampling, the number of samples is 60 respondents. The results of this study indicate that the elderly are in the category of 60-74 years (88.3%), the elderly are 75-90 years (11.7%), and the elderly are more than 90 years (0%). Gender category, male (50%), and female (50%). The category of hand washing behavior with a questionnaire is good (51.7%), quite good (36.7%), and not good (11.7%). The category of hand washing behavior with observation is good (3.3%), quite good (36.7%), and not good (60.0%). Â